Inquiry-Based Science and Technology Learning Assisted by Smart TV to Overcome Students' Difficulties in Understanding Abstract Science Concepts at SDIT Dhiya Ul Falah - Hayaturraiyan Hayaturraiyan; Lisnawati Lisnawati; Nita Sunarya Herawati; Nur Amalia Hildaini (Alifbata : Jurnal Pendidikan Dasar, 2026)
Characteristics development cognitive student School Base Still is at on stage operational concrete, so that Still difficulty in understand draft abstract. Study This aim For investigate effectiveness science-based learning inquiry Smart TV assisted for Overcome Difficulty Student in Understand Draft Science Abstract at SDIT Dhiya Ul Falah . Population study is all over Dhiya Islamic Elementary School students Ul Falah, which consists of 67 students And sample all over student class three totaling 13 students The approach used on study This is mixed-methods. The method used is quasi-experimental. Data collected through tests, observations, questionnaires. Instruments used covering instrument test, sheet observation, and questionnaire. Data analysis in quantitative use statistics descriptive, test normality use shapiro–wilk, test hypothesis, cohen's d For know big influence treatment. Whereas qualitative data analysis done with reduce data, present data , And withdraw conclusion . Results This show that integrate pedagogy based inquiry with interactive digital media in a way effective can increase understanding science abstract at SDIT Dhiya Ul Falah on science learning